2019
DOI: 10.4103/jlp.jlp_151_18
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical inflammation markers in hyperemesis gravidarum and ketonuria: A case–control study

Abstract: INTRODUCTION: Subclinical inflammation markers play a significant role in hyperemesis gravidarum (HEG). Simple hematological markers such as mean platelet volume (MPV), platelet distribution width (PDW), neutrophil-to-lymphocyte ratio (NLR), red cell distribution width (RDW), plateletcrit (PCT), and platelet-to-lymphocyte ratio (PLR) have been shown to reflect inflammatory burden and disease activity in several disorders. Ketonuria is a parameter used in the diagnosis of severe HEG, but its correlation with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
4
19
3
Order By: Relevance
“…High RDW values are thought to reflect increased inflammation and oxidative stress (23). However, in two recent studies, the RDW value of patients with HG was similar to that of the control group (24,25). In our study, similar results were obtained from these two studies.…”
Section: Muğla Sıtkı Koçman üNiversitesi Tıp Dergisi 2020;7(3):124-12supporting
confidence: 91%
See 2 more Smart Citations
“…High RDW values are thought to reflect increased inflammation and oxidative stress (23). However, in two recent studies, the RDW value of patients with HG was similar to that of the control group (24,25). In our study, similar results were obtained from these two studies.…”
Section: Muğla Sıtkı Koçman üNiversitesi Tıp Dergisi 2020;7(3):124-12supporting
confidence: 91%
“…However, Beyazit et al showed that MPV and PDW values in patients with HG were similar to healthy pregnant women (24). In the study of Cintesun et al, there was no significant difference between the HG group and the control group in terms of PCT, PDW, and MPV (25). In our study, PDW, MPV, and PCT values of both groups were similar.…”
Section: Muğla Sıtkı Koçman üNiversitesi Tıp Dergisi 2020;7(3):124-12supporting
confidence: 46%
See 1 more Smart Citation
“…Beyazıt et al [11] found no significant difference in terms of PDW level between hyperemesis and control groups. Çintesun et al [18] also found similar PDW levels among the groups. In our study, the mean PDW level in hyperemesis patients decreased significantly compared to the control group.…”
Section: Discussionmentioning
confidence: 67%
“…Lower levels of inflammatory markers, such as interleukin‐10, in late pregnancy have been shown to increase the risk of developing depressive symptoms postpartum 23 . This mechanism could also come into play for hyperemesis gravidarum and smoking during pregnancy, which have also been shown to be associated with changes in levels of inflammatory markers 24,25 …”
Section: Discussionmentioning
confidence: 99%